An original bionic algorithm for batch scheduling of traditional Chinese medicine extraction workshop: Simulated population growth blocked algorithm - Luo, Yabo; Hao, Haiqiang (Computers & industrial engineering, 2022)
•A new mathematical model of batch scheduling problem is established.•A new bionic algorithm, SPGBA, is proposed.•SPGBA can well solve function optimization problems and JSPs.•The batch scheduling problem of extraction workshop is well solved with SPGBA. Extraction process is one of the unique processes of traditional Chinese medicine production, and extraction workshop is a typical batch processing workshop. Due to the unique characteristics, such as the dynamic lot size of single batch, independent process of single batch, and the complex correlation in batch scheduling, the complexity of batch scheduling optimization of traditional Chinese medicine extraction workshop is much higher than that of general batch scheduling problems. In the real world production, the traditional Chinese medicine extraction workshop is also in a state of low efficiency. In order to solve the above problems, a new bionic algorithm, Simulated Population Growth Blocked Algorithm (SPGBA) is proposed by simulating the ecological balance mechanism, which also has the features of “dynamic”, “independent” and “complex correlation”. Firstly, the mathematical model of batch scheduling problem of traditional Chinese medicine extraction workshop is established; secondly, the bionic mechanism, principle and process of SPGBA are described in detail, and its Markov convergence is proved; thirdly, the effectiveness of SPGBA as a meta heuristic algorithm is verified by benchmarking comparative experiments; finally, SPGBA is used to solve the batch scheduling problem of real world extraction workshop, and a satisfactory solution is obtained.